2013
DOI: 10.2147/copd.s43992
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day measurement of patient-reported outcomes in exacerbations of chronic obstructive pulmonary disease

Abstract: BackgroundExacerbations of chronic obstructive pulmonary disease (COPD) are a major burden to patients and to society. Little is known about the possible role of day-to-day patient-reported outcomes during an exacerbation. This study aims to describe the day-to-day course of patient-reported health status during exacerbations of COPD and to assess its value in predicting clinical outcomes.MethodsData from two randomized controlled COPD exacerbation trials (n = 210 and n = 45 patients) were used to describe bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Furthermore, a recent work in which the patients were monitorised daily during an exacerbation, showed that the absence of improvement in CCQ symptoms score and impaired lung function were independent predictors of treatment failure [28]. Concurrent with our results, the authors find the rate and pattern of recovery very similar in outpatients and inpatients [28]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, a recent work in which the patients were monitorised daily during an exacerbation, showed that the absence of improvement in CCQ symptoms score and impaired lung function were independent predictors of treatment failure [28]. Concurrent with our results, the authors find the rate and pattern of recovery very similar in outpatients and inpatients [28]. …”
Section: Discussionsupporting
confidence: 85%
“…Using weekly measurements, an impairment of 0.20 points had a positive predictive value of 43.5% and a negative predictive value of 90.8% for the onset of an exacerbation in the next week [27]. Furthermore, a recent work in which the patients were monitorised daily during an exacerbation, showed that the absence of improvement in CCQ symptoms score and impaired lung function were independent predictors of treatment failure [28]. Concurrent with our results, the authors find the rate and pattern of recovery very similar in outpatients and inpatients [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong supporting evidence for the reliability, validity, and responsiveness of the CCQ 42,55. The CCQ has also been shown to be very sensitive to clinical improvement after smoking cessation,16,56 and during and after exacerbations 57. Further, contrary to expectations, the total CCQ score correlates well with lung function (as assessed by FEV 1 percent predicted) in patients with COPD, although this relationship was limited to patients with GOLD airflow limitation grades 1–3 16.…”
Section: Clinical Copd Questionnairementioning
confidence: 92%
“…Although this score is similar to our results, the time at which the CCQ score was measured is different, as we measured the CCQ on admission to the SNF. In the study by Kocks et al , 21 the CCQ total score improved rapidly during hospital stay, with a mean score of 2.3 on day 7. These results seem to confirm that our population indeed consisted of those patients who failed to recover during hospital stay.…”
Section: Discussionmentioning
confidence: 88%
“…This can be explained by the fact that our population suffered from a recent exacerbation and that exacerbations have a negative effect on health status. Recently, Kocks et al 21 reported data from two randomised controlled COPD exacerbation trials on the day-to-day course of patient-reported health status (as measured with the CCQ) during exacerbations. They reported results from 210 COPD patients admitted to hospital for an acute exacerbation (mean age 70.6 years, mean FEV 1 : 37% of predicted); the CCQ total score on admission to the hospital was 3.3 (±0.93).…”
Section: Discussionmentioning
confidence: 99%